Christmas tree with the Star of Bethlehem - Mumbai Archive Project (Jio Institute, 2024)
Over time, the celebrations at the Club of St. Anthony have become muted. During Christmas, the manager, Mr Antonio Baretto, makes arrangements for decorating the club with lights. In 2023, he installed a Christmas tree with the Star of Bethlehem and a miniature representation of the nativity scene (the birth of Jesus in a manger) in the reception hall.